Assessment of Feasibility for Biodigestion of Cattle Waste in Gwalior City, India - Ram Kishore Shukla; Rakesh Kumar Shrivastava; Sudhir Singh Bhadauria; Shrey Jain (Advances in Civil Engineering)
Different biodegradable waste may indeed be processed by biodigesters to generate biogas, a clean and sustainable source of energy. Different digesters are classified according to their digestive process, which is either aerobic or anaerobic. The rate at which organic waste is loaded, the temperature, the amount of dilution, etc., all affect the size of the digesters. A biodigester typically needs a relatively steady atmosphere as well as ongoing agitation. Additionally, it necessitates a large land area. Although it has numerous advantages, the nature of the feedstock is the main factor on which the potential of biogas production depends, as well as the design of the reactor and operational parameters. Though many authors attempted to establish the effect of various factors on the process of biodigestion of food waste, very few studies on reactor design to achieve maximum biogas production were reported. The current study focuses on the use of a reactor with multiple stages that requires a smaller footprint to increase the rate of gas production from solid substrates. In the study, an experiment was attempted to determine the effect of substrate composition, food waste size, and multiple stages inside the reactor on biogas production. It has been found from the results that agricultural and environmental sustainability associated with livestock waste can reduce pollution risk considerably through biodigestion. It has also been found that stages inside the reactor do have an effect on gas production, which has been increased by up to 30%.